Plasticity of Lateral Root Branching in Maize - Yu, Peng; Hochholdinger, Frank; Li, Chunjian (Frontiers in Plant Science, 2019)
Extensively branched root systems can efficiently capture soil resources by increasing their absorbing surface in soil. Lateral roots are the roots formed from pericycle cells of other roots that can be of any type. As a consequence, lateral roots provide a higher surface to volume ratio and are important for water and nutrients acquisition. Discoveries from recent studies have started to shed light on how plant root systems respond to environmental changes in order to improve capture of soil resources. In this Mini Review, we will mainly focus on the spatial distribution of lateral roots of maize and their developmental plasticity in response to the availability of water and nutrients.